The Experimental Study Of Using Array Of Wireless Accelerometer Sensors For Impact Loads On The Amphibious Float Model Test - Nugroho, Wibowo Harso; Purnomo, Nanang Joko Hadi; Arianti, Erdina; Mujahid, Ahmad Syafi'ul; Priohutomo, Kusnindar; Sahlan,; Permana, Chandra; Adinanta, Hendra (International Journal of Marine Engineering Innovation and Research, 2025)
Maritime tourism in Indonesia holds substantial potential for future growth, contributing to the well-being of coastal communities. Amphibious aircraft, capable of taking off and landing on both water and land, provide an efficient means for tourists to explore the country's diverse regions. Accurately predicting hydrodynamic loads is therefore essential to ensuring the reliability of amphibious float structures. This study aims to validate the feasibility of replacing cable-based accelerometer sensors with wireless alternatives to measure impact loads on an amphibious aircraft float model. Accelerometers were mounted on the float model, and impact loads were tested using a launcher in a mechanical workshop prior to hydrodynamic tests in a water tank. The data revealed that the sensors effectively captured impact loads, with measurements averaging a 3.7% deviation from theoretical values. The maximum impact force recorded was 1.98 g, and the minimum was 0.61 g. These findings support the use of wireless systems for hydrodynamic impact load testing in water tank environments.